Themes Identified in Implemented SDGs for Developing Indicators of Public Library Services: A Scoping Review - Widiyawati, Anita Tri; Kanyarat Kwiecien; Lan Thi Nguyen (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Public libraries have a primary role in providing everyone with access to information. This research is based on the limited identification of themes that can be used as a reference in implementing services to support the SDGs comprehensively. This study aims to identify themes related to developing trends that can be used as a reference in developing public library service indicators to implement SDGs-based services. A scoping review was used in this study, with 5 stages by Arksey and O’Malley (2005) and Levac, Colquhoun, and O’Brien (2010), that is: Step One: Research Question, Step Two: Identification of Relevant References, Step Three: Selection of References and Data, Step Four: Charting the Data, Step Five: Collating, Summarizing, and Reporting Results. Research findings show that people's information needs depend on their social and economic background and living conditions (e.g., environmental conditions and a safe place). Strong collaboration at local, national, and global levels, including collaboration between public libraries and communities, continuous innovation, and building stable big data, can affect public libraries' achievement in supporting the SDGs.